Pemanfaatan Teknologi Barcode untuk Manajemen Inventarisasi Mebeler Berbasis Aplikasi Mobile (Studi Pasa Fakultas Ekonomi Bisnis dan Informatika Universitas Bina Sehat PPNI Mojokerto) - Ristono, Joko; Ardiantoro, Luki; Gumilar, Eko (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The research at the Faculty of Business Economics and Informatics, Bina Sehat University, PPNI Mojokerto, aims to address challenges in manual furniture inventory management, including difficulties in tracking furniture quantities, locations, and conditions. To solve this, a Smartphone-Based Furniture Inventory Reporting Management Application was developed. Data collection methods included observation of furniture management processes (sorting into feasible, less feasible, and unsuitable categories) and literature studies for application development. The prototype model, based on the SDLC method, was used with tools like Visual Studio Code and XAMPP. The application utilizes a barcode scanner to input furniture codes, organize data, and serve as a reference for procurement and sorting. It requires mobile internet for optimal functionality and compatibility across smartphones. The result is an efficient tool for managing furniture inventories..